The comprehensive and progressive Trans-Pacific Partnership : analysis and commentarythe - Huerta-Goldman, Jorge Alberto; Gantz, David A. (Cambridge : Cambridge University Press, 2022)
The Comprehensive and Progressive Agreement for Trans-Pacific Partnership among eleven key nations of the Pacific Rim has already expanded trade and economic cooperation among the Parties. It also serves to encourage political cooperation among them and has served as a model for future 'wide and deep' free trade agreements. The chapters of this book will provide readers with a detailed understanding of the CPTPP's coverage, including provisions relating to tariff elimination, customs rules of origin, agriculture, sanitary and phytosanitary measures, technical barriers to trade, telecommunications, intellectual property, investment and investor-state arbitration, financial and other services, government procurement, state-owned enterprises, electronic commerce and digital trade, small and medium-sized enterprises, competition law, labor and environmental protection, dispute settlement, and many others. No international lawyer, economist, trade negotiator, or enterprise can afford not to take advantage of the opportunities for business that the CPTPP offers. This book has been written by CPTPP negotiators, experts, and practitioners.
Introduction : The Trans-Pacific Partnership becomes the comprehensive and progressive agreement for TPP / David A. Gantz and Jorge Huerta-Goldman -- TPP, US Congress and the Trade Promotion Authority / Sheridan S. McKinney and John Gilliland -- The TPP, a horizontal overview / Roberto Zapata Barradas -- Market access for trade in goods negotiations in the TPP / Cesar Guerrero and Felix Gonzalez Saenz -- Trade provisions as legos? : how Chapter 2 of the TPP was influenced by WTO negotiations and prior US trade deals / Roy Santana -- TPP, agricultural trade and food security / Ekaterina Krivonos, Daneswar Poonyth and Mischa Tripoli -- Rules of origin and origin procedures / Luis Ricardo Rodriguez Meneses -- Trade in textiles and apparel goods / Rupa Ganguli and Jorge A. Huerta Goldman -- How far beyond the TFA? Trade facilitation in the WTO and the TPP / Carlos Gabriel Enriquez Montes -- Treatment of trade remedies under the Trans-Pacific Partnership, Chapter 6 / David A. Gantz -- SPS chapter under the TPP agreement and its implications / Yuka Fukunaga -- Technical barriers to trade / Jorge A. Huerta Goldman -- Addressing the right to regulate in the CPTPP investment chapter: identifying new treaty practice / Rodrigo Monardes, Ana Novik and Carlos Portales -- Protecting Investment under NAFTA the Trans-Pacific Partnership and the comprehensive and progressive TPP / David A. Gantz -- The Trans-Pacific Partnership as a development of the Australia-United States free trade agreement : services liberalization and investment protection / Tania Voon and Andrew D. Mitchell -- Services overview : background, strategy and solutions / Amb Peter Allgeier -- Cross-border trade in services (Chapter 10) and temporary entry for business persons (Chapter 12) / Guillermo Malpica Soto -- Financial services / Juan A. Marchetti -- Telecommunications chapter in the TPP Gerardo Meza Grillo -- Understanding the TPP agreement e-commerce chapter / Ed Brzytwa, Stephen Ezell and Nigel Cory -- Government procurement in the Trans-Pacific Partnership Agreement : a global beachhead for market access and good governance Robert D. Anderson, Philippe Pelletier and Christopher R. Yukins -- TPP's competition policy chapter : towards convergence / Juliana Nam -- Rules for state-owned enterprises in Chapter 17 of the Trans-Pacific Partnership Agreement : balancing market-oriented discipline and policy flexibility for states / Iain Sandford and Jan Yves Remy -- Non-commercial assistance rules in the TPP : a comparative analysis with the SCM Agreement / Yoshinori Abe and Takemasa Sekine -- IP in the TPP: how far beyond the existing FTAs does it go? / Maximiliano Santa Cruz Scantlebury and Denisse Perez -- Strengthening labor rights in the Trans-Pacific Partnership Agreement : a lost opportunity? / Desiree LeClercq and Karen Curtis -- TPP trade and environment chapter / Christopher O'Toole -- Horizontal regulatory coherence aspects of the TPP Phoenix X. F. Cai -- Transparency and anti-corruption Jorge A. Huerta Goldman -- State-to-state dispute settlement under TPP Chapter 28 and NAFTA Chapter 20 / David A. Gantz -- Initial provisions, administrative provisions, exceptions and final provisions (TPP Chapters 1, 27, 29 and 30) / David A. Gantz.
Title from publisher's bibliographic system (viewed on 11 Nov 2021).
Keywords: Comprehensive and Progressive Agreement for Trans-Pacific Partnership -- (2018 March 8).; Foreign trade regulation -- Pacific area; International economic relations -- Pacific Area